Plant developmental stage drives the assembly and functional adaptability of endophytic microbial communities - Yang, Min; Wang, Jindan; Qi, Ying; Gao, Penghua; Li, Lifang; Guo, Jianwei; Zhao, Yongteng; Liu, Jiani; Chen, Zebin; Zhao, Jianrong; Yu, Lei (Frontiers in Microbiology, 2025)
IntroductionThe seeds of Amorphophallus muelleri represent a unique category of herbaceous seeds that arise from triploid apomixis. They necessitate an exceptionally protracted maturation phase of 8 months, followed by a dormancy period of 4 months, before they can germinate and give rise to fully formed new plants. Currently, the connection between endophytic microbial communities in A. muelleri seeds and the host plant’s development is largely unexplored.MethodsHerein, we analyzed the temporal dynamics of the endophytic bacterial and fungal communities from seed germination to seedling establishment (seven stages) through amplicon sequencing.Results and discussionThe results showed that plant developmental stage explained the large variation in endophytic bacterial and fungal communities in A. muelleri and that multiple microbial attributes (e.g., α, β-diversity, community composition, and bacterial and fungal ecological networks) are driven by the developmental state of A. muelleri. Metagenomic analyses further indicated that the four stages after rooting have higher microbial functional diversity. Microbial functional genes involved in cell wall/membrane/envelope biogenesis, inorganic ion transport and metabolism, and carbon degradation were abundant in A. muelleri seeds from Stage 1 to Stage 3 (before rooting). From Stage 4 to Stage 7 (after rooting), microbial functional genes involved in the carbon, nitrogen and phosphorus cycles, starch and sucrose metabolism, and energy production and conversion were more abundant. Coincidentally, more abundant Proteobacteria, and Basidiomycota taxa related to carbon degradation were found in stages 1-3, while more Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium and Stenotrophomonas taxa associated with nitrogen cycling and plant growth promotion were observed in stages 4-7. These findings have greatly improved our basic understanding of the assembly and functional adaptability of the endophytic microbiome during A. muelleri plant development and are helpful for the mining, development and utilization of functional microbial resources.